2004
DOI: 10.1258/0956462042395230
|View full text |Cite
|
Sign up to set email alerts
|

Seeking and engaging in internet sex: a survey of patients attending genitourinary medicine clinics in Plymouth and in London

Abstract: We conducted a survey of patients attending two GUM clinics to evaluate the use of the internet for seeking sexual partners and for seeking on-line sexual health information. Prevalence of internet sex-seeking (ISS) was 11% (57/500) in Plymouth and 21% (50/237) in London. ISS was more common among men who have sex with men (MSM) (43/92 = 47%) than men who have sex with women (MSW) (38/280 = 14%, P< 0.0001) and more common amongst MSW than women who have sex with men (WSM) (25/350 = 7%, P = 0.007). In both samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…On the other hand, a recent analysis found that heterosexuals who used the Internet to find partners were at lower risk for STDs than other heterosexual STD clinic patients21, highlighting the complexity of how the Internet may affect STD risk and transmission dynamics. Little information is available regarding Internet and email use among STD clinic patients and the potential utility of using both to improve clinical care and facilitate STD-related research1719. The Internet has been used to arrange for syphilis testing and provide test results10, 14, to follow-up on partners of reported syphilis cases13, to provide test results to all clients of an STD clinic22, and to collect sexual diary information for a genital human papilloma virus research study23.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a recent analysis found that heterosexuals who used the Internet to find partners were at lower risk for STDs than other heterosexual STD clinic patients21, highlighting the complexity of how the Internet may affect STD risk and transmission dynamics. Little information is available regarding Internet and email use among STD clinic patients and the potential utility of using both to improve clinical care and facilitate STD-related research1719. The Internet has been used to arrange for syphilis testing and provide test results10, 14, to follow-up on partners of reported syphilis cases13, to provide test results to all clients of an STD clinic22, and to collect sexual diary information for a genital human papilloma virus research study23.…”
Section: Discussionmentioning
confidence: 99%
“…In 1999, 40% of San Francisco STD clinic patients reported having Internet access at home and, of these persons, 84% had accessed the Internet in the past 6 months17. In 2000–2001, 46% of Denver Metro Health STD clinic patients had Internet access, of these 73% at home18, while in 2002–2003, 77% of patients at a genitourinary medicine (GUM) clinic in Plymouth, U.K. and 90% of patients at a GUM clinic in London, U.K. had Internet access19. In 2006, 63% of MSM seen in a Seattle, Washington public HIV clinic reported home Internet access28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples of men visiting the two venues were obtained from a sampling frame of brothels and the most popular internet sex forums in Singapore. Most previous studies have recruited online sex seekers from attendees of STI clinics 1 18. The high response rate and time location sampling also support the generalisability of the findings of the brothel group to all licensed brothels in Singapore.…”
Section: Discussionmentioning
confidence: 65%
“…Dessa forma, a prevalência de comportamento sexual de risco e de infecção pelo HIV entre HSH ainda é elevada, em geral (Benotsch et al, 1999;Colby, 2003;Wong e Tang, 2004;MacKellar et al, 2005;Treisman et al, 2005). (Benotsch et al, 1999;Rietmeijer et al, 2001;Malu et al, 2004…”
Section: Compulsão Sexualunclassified